Techno-economic analysis of solar home system (SHS) in Cambodia / Masoud Sarraf - Masoud, Sarraf (2013)
Providing rural areas with a feasible electrification system has always been a mind-blowing issue for the policy makers in different countries. A well-established electrification system can bring about numerous advantages for the people living in these areas. Improving the condition of life, health and education as well as the public growth are among these benefits. Cambodia, with a population of 15 million, is one of those countries with a significant potential of renewable energies yet with insufficient amount of exploitation. Solar energy as one of the most available and cheapest sources of energy can be properly utilized in Cambodia to make up for an amount of this deficiency in sustainable energy harvesting. In this study, the feasibility of using Solar Home System (SHS) for a rural area in Cambodia with no access to electricity is investigated both from economical and technical aspects. Three cases of electricity loads was specified and closely analysed for this purpose. These cases included low (9W for 8h) , average (36 W for 3 h) and high (63 W for 4 h). For these cases, 40Wp, 55Wp and 2×65Wp PV options were found to be suitable resulted from technical analysis. From economical analysis, annualized life cycle cost (ALCC) was also determined theoretically. The three cases showed 74.46, 102.38, 241.99 (kWh) values for ALCC. Besides, the levelised unit cost of electricity (LUCE) was calculated to be 1.13, 0.71 and 0.99 (US$./kWh) for the mentioned case studies. Comparing the analytical results with HOMER simulation, nearly 90% agreement was reached between the two methods. Finally, after comparing each proposed case with grid extension option, the most feasible choice for the purpose of electrification of this special area was recognized.